The Application of Incretin-Based Pharmacotherapy in the Contemporary Management of Type 2 Diabetes: A Review of the Literature - Waszczyński, Jakub; Kulej, Wojciech; Biesiada, Wiktor; Kulej, Piotr; Woźniak, Justyna; Kmieć, Justyna Weronika; Chernysh, Anna Mariia; Dusińska, Aleksandra; Fuczyło, Kamila; Stankević, Karolina (Quality in Sport, 2025)
Introduction Type 2 diabetes is a critical global health issue due to its rising prevalence and severe complications, including cardiovascular diseases, chronic kidney disease, and neuropathies, which reduce quality of life and increase mortality risk. While metformin remains a cornerstone of treatment, incretin-based therapies like GLP-1 receptor agonists and DPP-4 inhibitors provide additional benefits, including glycemic control, weight management, and organ protection, making them essential in personalized care. Aim of the Study This study evaluates the mechanisms, efficacy, and benefits of GLP-1 receptor agonists and DPP-4 inhibitors in improving glycemic control, reducing cardiovascular risk, managing weight, and protecting renal function. Materials and Methods Data was sourced from recent clinical trials and literature (post-2020) from PubMed, Google Scholar, Lancet, New England Journal of Medicine, Nature, American Diabetes Association, Research Gate. Results GLP-1 receptor agonists demonstrated significant benefits, including a 27% reduction in major adverse cardiovascular events (MACE), a 32% decrease in kidney disease progression, and notable weight loss (e.g., 15.2% with semaglutide). These drugs also improved glycemic and metabolic parameters, though initial gastrointestinal side effects were common but temporary. DPP-4 inhibitors showed nephroprotective effects, reducing albuminuria and slowing eGFR decline, and were associated with a lower hypoglycemia risk compared to sulfonylureas, particularly in advanced CKD. While less effective in weight management, they offered a weight-neutral option for patients with mild hyperglycemia or advanced CKD. GLP-1 receptor agonists are ideal for high-risk or obese patients due to their strong glycemic and weight benefits, whereas DPP-4 inhibitors are safer for those with advanced CKD.